Design of an Automatic Cooling System for Microcontroller-Based Solar Panels - Azizah, Nurul; Yanto, Doni Tri Putra; Pulungan, Ali Basrah; Dewi, Citra (Jurnal Teknik Elektro Indonesia, 2025)
The increasing need for electrical energy and its central role requires electrical energy suppliers to find new plants in order to meet consumer needs and avoid an electrical energy crisis. Utilization of solar energy through solar panels is an alternative to meet these needs. However, in the process of converting solar energy into electrical energy, the temperature of solar panels increases, causing the performance and efficiency of solar panels to decrease. Solar panels can produce the best power at temperatures of 25oC-35oC. When there is an increase in temperature by 1 ° C, the power generated decreases by 0.4%. An automatic cooling system is a solution that can be used to prevent the solar panel temperature from exceeding its optimal temperature limit. The solar panel cooling system made works on 10Wp solar panels with control from Arduino Uno, with inputs in the form of ACS712 sensors, DC voltage sensors, DHT11 sensors and RTC DS3231. The outputs are relays, LCD and micro-SD module. The methodology used in the research involves the design, implementation, and testing stages of the system prototype. After testing the prototype in the form of a comparison between solar panels with a cooling system and without a cooling system. It was found that when using a cooler, the average power generated was 9.1W. While solar panels without cooling can only produce an average power of 2.5W. This proves that the cooling system made can increase the output power.